COMMUNITY-BASED NUTRITION INTERVENTION TO REDUCE STUNTING IN TENGANAN VILLAGE: A COLLABORATION BETWEEN UNIVERSITAS WARMADEWA AND WASEDA UNIVERSITY - Sri Masyeni; Gita Pritayanti Dinar; Pasek Mangku; Saraswati Laksmi Dewi; Tomoko Wake (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
Stunting is a chronic, nutrition-related growth disorder that impacts both physical growth and cognitive development, with varying prevalence across different regions. Tenganan Village in Karangasem faces significant challenges regarding stunting, which necessitate integrated interventions. The objective of this project is to improve nutrition knowledge, promote balanced dietary practices using locally available foods, and enhance community capacity to reduce the risk of stunting in Tenganan Village. This includes socializing with partners, conducting Focus Group Discussions (FGDs), providing interactive nutrition education on stunting prevention, showing educational videos, demonstrating the Isi Piringku plates, and distributing stunting prevention materials such as chickens, fish, vegetables, and groceries. The pre-test mean score was 21.2, while the post-test mean score increased to 67.6, indicating a 68.6% improvement in knowledge about the Isi Piringku method. This study was supported by local food security materials provided by Japanese partners. In conclusion, the intervention successfully enhanced nutrition knowledge and practical skills for preparing nutritious meals using locally sourced ingredients, with the potential to reduce stunting rates if these efforts are sustained.